Sustainable Food Home Area (KRPL) Policy in Sumbergondo Village, Batu City : an Implementation Approach - Sihidi, Iradhad Taqwa; Titania, Devi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
Food security is an important issue to be studied concerning the welfare of a country. The government has tried to build and develop food security by utilizing land through the KRPL program. The Batu City Food Security Service launched the KRPL program to utilize yard land. Sumbergondo Village is the location for implementing KRPL because of the potential for land and nature. So, this study aims to determine the implementation of the KRPL policy in improving Food Security. The research was conducted in Sumbergondo Village, Bumiaji District, Batu City. The method used in this study is a qualitative research method using primary and secondary data sources. Observation, interviews, and documentation are used to carry out data collection techniques. This research shows that the implementation of the KRPL policy in Sumbergondo Village is going well, seen from the aspects of policy implementation, namely through an analysis of good and supportive environmental conditions and inter-organizational relationships that run according to existing structures. Organizational resources include human and financial resources that accept and run the program optimally. It is up to the characteristics and abilities of program implementing agents to improve the food security of the Sumbergondo Village community through the use of the KRPL program land.